Situation Report: Poland, 8 June 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Exchange of Treaty Ratification Documents between Poland and West Germany; Establishment of Diplomatic Relations The Aftermath of the Nixon Visit Foreign Relations New Editorial Line for Trybuna Ludu New Appointments